In Vitro and in Vivo Comparison of Binding of 99m-Tc-Iabeled Anti-CEA MAb F33-104 with 99m-Tc-labeled Anti-CEA MAb BW431/26 - Watanabe, N.; Oriuchi, N.; Sugiyama, S.; Kuroki, M.; Matsuoka, Y.; Tanada, S.; Murata, H.; Inoue, T.; Sasaki, Y. (Nuklearmedizin - NuclearMedicine, 1999)
Aim: The purpose of this study was to assess the potential for radioimmunodetection (RAID) of murine anti-carcinoembryonic antigen (CEA) monoclonal antibody (MAb) F33-104 labeled with technetium-99m (99m-Tc) by a reduction-mediated labeling method. Methods: The binding capacity of 99m-Tc-labeled anti-CEA MAb F33-104 with CEA by means of in vitro procedures such as immunoradiometric assay and cell binding assay and the biodistribution of 99m-Tc-labeled anti-CEA MAb F33-104 in normal nude mice and nude mice bearing human colon adenocarcinoma LS180 tumor were investigated and compared with 99m-Tc-labeled anti-CEA MAb BW431/26. Results: The in vitro binding rate of 99m-Tc-labeled anti-CEA MAb F33-104 with CEA in solution and attached to the cell membrane was significantly higher than 99m-Tclabeled anti-CEA MAb BW431/261 (31.4 ± 0.95% vs. 11.9 ± 0.55% at 100 ng/mL of soluble CEA, 83.5 ± 2.84% vs. 54.0 ± 2.54% at 107 of LS 180 cells). In vivo, accumulation of 99m-Tc-labeled anti-CEA MAb F33-104 was higher at 18 h postinjection than 99m-Tc-labeled anti-CEA MAb BW431/26 (20.1 ± 3.50% ID/g vs. 14.4 ± 3.30% ID/g). 99m-Tcactivity in the kidneys of nude mice bearing tumor was higher at 18 h postinjection than at 3 h (12.8 ± 2.10% ID/g vs. 8.01 ± 2.40% ID/g of 99m-Tc-labeled anti-CEA MAb F33-104, 10.7 ± 1.70% ID/g vs. 8.10 ± 1.75% ID/g of 99m-Tc-labeled anti-CEA MAb BW431/26). Conclusion: 99m-Tc-labeled anti-CEA MAb F33-104 is a potential novel agent for RAID of recurrent colorectal cancer.
Keywords: Radioimmunodetection; 99m-Tc-labeled anti-CEA MAb F33-104; 99m-Tc-labeled anti-CEA MAb BW431/26; reduction-mediated labeling method; renal uptake